2018
DOI: 10.1038/s41598-018-22015-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Water Confinement in Disordered Aluminosilicate Subnanopores

Abstract: The porous structure and mass transport characteristics of disordered silicate porous media were investigated via a geometry based analysis of water confined in the pores. Disordered silicate porous media were constructed to mimic the dissolution behavior of an alkali aluminoborosilicate glass, i.e., soluble Na and B were removed from the bulk glass, and then water molecules and Na were introduced into the pores to provide a complex porous structure filled with water. This modelling approach revealed large sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 60 publications
2
13
1
Order By: Relevance
“…1,[20][21][22][23][24][25] In particular, the formation of several individual layers with largely different porosity inside a single SAL (exp. QBG-90/150) is difficult to explain by a leaching model that considers (i) the SAL as a residual and restructured glass and (ii) its porosity as a reflection of the free space created by the selective removal of certain network formers and modifiers from the glass, 26 and (iii) a transitional zone presented as hydrated glass 2 ahead of the SAL. On the other hand, the structural, textural, and isotopic features are fully consistent with the ICDP model that considers the SAL as being an amorphous silica precipitate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[20][21][22][23][24][25] In particular, the formation of several individual layers with largely different porosity inside a single SAL (exp. QBG-90/150) is difficult to explain by a leaching model that considers (i) the SAL as a residual and restructured glass and (ii) its porosity as a reflection of the free space created by the selective removal of certain network formers and modifiers from the glass, 26 and (iii) a transitional zone presented as hydrated glass 2 ahead of the SAL. On the other hand, the structural, textural, and isotopic features are fully consistent with the ICDP model that considers the SAL as being an amorphous silica precipitate.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, it is assumed that the porosity in the gel layer directly reflects the free space created in the glass by the removal of cations from the glass structure. 26 Although this interdiffusion-based ion exchange or leaching model became widely accepted, particularly in the glass community, there has been a long dispute about the passivating effect of the SALs that is reflected by an experimentally observed drop in the corrosion rate with time. 27 It has been suggested that the SAL may be protective against further glass corrosion by pore closure or by restructuring of the hydrated glass, forming a passivating reactive interphase (PRI).…”
Section: Introductionmentioning
confidence: 99%
“…Water transport, dynamics, and structure in nano-porous materials have been shown to be different from those in the bulk. 9,20,21,32,59 It was shown for alteration layers formed on ISG corroded in aqueous solutions that there is an evolution of pore size in the layers with corrosion time and it is accompanied by a structural rearrangement of the alteration layer. 9,40 In consequence, the transport and behavior of water and mobile elements would change with the evolution of alteration layer and they need to be considered in theoretical modeling and computational simulation of glass corrosion.…”
Section: Xps Depth Profilementioning
confidence: 99%
“…In Molecular Dynamics (MD) simulations, the modeling of dissociation of water and reaction with silicates is a critical component simulating glass‐water interactions . While the transport of glass components into solution can be modeled with nonreactive force fields . use of a reactive potential is critical for analyzing all the reactions and material transport inside the glass and solution.…”
Section: Introductionmentioning
confidence: 99%
“…27,30 While the transport of glass components into solution can be modeled with nonreactive force fields. 31,32 use of a reactive potential is critical for analyzing all the reactions and material transport inside the glass and solution. Recent improvements of reactive MD force fields have allowed for several advances in the modeling of silica-water interactions.…”
mentioning
confidence: 99%